Population Dynamics at the Range Margin: Implications of Climate Change on Sublittoral Blue Mussels (Mytilus trossulus) - Westerbom, Mats; Mustonen, Olli; Jaatinen, Kim; Kilpi, Mikael; Norkko, Alf (Frontiers in Marine Science, 2019)
Examining changes in abundance and demographic rates at species distribution margins may provide the first signs of broader species responses to environmental change. Still, the joint impact of space and time have remained relatively unstudied in most marginal regions. In order to examine the influence of climate variability on mussel distribution patterns, we monitored three sublittoral and marginal blue mussel (Mytilus trossulus) populations, spaced along a salinity gradient. Densities and biomasses peaked towards the saltier parts of the study area and showed relatively larger variations towards the low saline edge. Temporally, the areas showed a consistent increase in abundance after a synchronized large-scale recruitment event, which was followed by a decline in population size, occurring much faster towards the very range edge. Salinity, temperature, winter severity and wave exposure explained most of the spatiotemporal variation in mussel abundances and adults showed positive effects on recruit abundance. We show empirically that the dynamics of edge populations are not driven by large changes in climate variables but that small spatial and temporal changes in key environmental variables have large and non-linear population level effects. Our results also show that fluctuating recruitment is a key factor for population stability affecting the storage potential of marginal populations, which dramatically decrease towards the edge. Our study provides a window into future population patterns and processes that drive marginal mussel populations in an altered sea characterised by rising temperature and declining salinity.